Environmental Issues and Social Inclusion in a Sustainable Era Proceedings of the 2nd International Conference on Humanities and Social Sciences (ICHSOS 2022), Malang, Indonesia, 1-2 July 2022 - Robbie, R. Iqbal; Roziqin, Ali; Deniar, Shannaz Mutiara; Praharjo, Ardik; Roz, Kenny (Taylor & Francis, 2024)
The Sustainable Development Goals (SDG) and the Paris Climate Agreement are examples of initiatives where countries show recognition of their interconnected interests and goals. This is particularly evident in the case of global environmental issues because they require global decision-making. The emergence of global environmental issues such as climate change, marine pollution and biodiversity loss has brought new challenges to governance and requires political support and innovation of global public policies. In addition, many social problems arise because of the environmental crisis. Environmental Issues and Social Inclusion in a Sustainable Era discusses environmental and social inclusion in a socio-economic perspective. The contributions analyse the management of global environmental problems at local, national and international levels, with a special focus on multilevel governance, innovative public policies, and economic development finance and business. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license. Funded by Universitas Muhammadiyah Malang.